2022
DOI: 10.1111/are.15727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L‐carnitine supplementation on growth performance, histomorphology, antioxidant and immune function of Rhynchocypris lagowskii fed dietary fish oil replaced with corn oil

Abstract: The effects of L‐carnitine (LC) and dietary lipid on the growth and health of farmed fish are still conflicting. This study aimed to explore the effects of LC supplementation and dietary fish oil replacement by corn oil on growth performance, antioxidant, immune function and histomorphology of Rhynchocypris Lagowskii. Six diets were evaluated as follows: dietary fish oil as 50% and 100% replacement by corn oil, and differing in LC supplementation (0 and 400 mg/kg), were tested in R. Lagowskii for 8 weeks. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In contrast, some studies have shown results in poor growth in marine and freshwater fishes that primary dietary inclusion levels of SO (Chen et al, 2020;Jin, Mu et al, 2018). Similarly, Wang et al, (2022) showed no significant effects between the FO diet and VO diet on WG, SGR, and PER for Rhynchocypris lagowskii. Similar results are reported that no negative effects on growth performance were observed because of the substitute of dietary FO with VO of some fish species blunt snout bream, (Megalobrama amblycephala), red hybrid tilapia (Oreochromis sp), rainbow trout (Oncorhynchus mikyss) and marine fish European sea bass (Dicentrarchus labrax) , Japanese Seabass (Lateolabrax japonicus) (Roy et al, 2020;Torrecillas et al, 2017).…”
Section: Growth Performancementioning
confidence: 84%
See 4 more Smart Citations
“…In contrast, some studies have shown results in poor growth in marine and freshwater fishes that primary dietary inclusion levels of SO (Chen et al, 2020;Jin, Mu et al, 2018). Similarly, Wang et al, (2022) showed no significant effects between the FO diet and VO diet on WG, SGR, and PER for Rhynchocypris lagowskii. Similar results are reported that no negative effects on growth performance were observed because of the substitute of dietary FO with VO of some fish species blunt snout bream, (Megalobrama amblycephala), red hybrid tilapia (Oreochromis sp), rainbow trout (Oncorhynchus mikyss) and marine fish European sea bass (Dicentrarchus labrax) , Japanese Seabass (Lateolabrax japonicus) (Roy et al, 2020;Torrecillas et al, 2017).…”
Section: Growth Performancementioning
confidence: 84%
“…At high dietary SO including, the body lipid accumulation more compared to other fish gropus. Similarly the replacement of SO for FO increased tissue fat content in grass carp Ctenopharyngodon Idella (Liu et al, 2022); large yellow croaker (Du et al, 2017) and seabream (Izquierdo et al, 2015) .…”
Section: Proximate Compositionmentioning
confidence: 98%
See 3 more Smart Citations